Pengaruh Posisi Prone Dalam Meningkatkan Saturasi Oksigen dan Mengurangi Sesak Pada Pasien Gangguan Pernapasan: Systematic Review - Adenan, Antelina (Poltekkes Kemenkes Banjarmasin, 2025)
Background. Respiratory distress is one of the leading causes of morbidity and mortality, especially in vulnerable populations such as patients with chronic lung disease, pneumonia and acute respiratory distress syndrome (ARDS). One non-invasive approach that has been shown to be effective in increasing oxygen saturation and reducing shortness of breath is the prone position. This position refers to the prone sleeping position, where the patient lies face down. Objective to increase oxygen saturation and reduce shortness of breath Method A systematic review approach through searching articles tailored to the formulation of research questions with the PEO formulation in seven databases namely Scopus, ScienceDirect, Pubmed, Proquest, Sage Journals, Oxford, Wiley Results in the analysis it was found that the prone position is very effective in increasing oxygen saturation and reducing patient shortness of breath especially when combined with other pharmacological treatments. Conclusion is that the prone position performed for 12 hours/day is very effective in increasing saturation, increasing oxygenation and reducing the number of intubated patients.